Membangun Ketahanan Keluarga Untuk Mencegah Bentuk Kejahatan Narkotika Yang Terorganisasi Dengan Basis Keluarga - Pakpahan, Hendra; Bakhtiar, Reza; Ma'arif, Nasrul (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
The phenomenon of family involvement in organized narcotics crime emerged in Indonesia when Lian Silas, the father of a narcotics lord - Fredy Pratama, was involved in alleged money laundering from the proceeds of his son's illicit narcotics business. Not only that, Fredy also involved other family members. In fact, this phenomenon is nothing new in cases of organized narcotics crime, as the Italian mafia group is also closely linked to the role of the family in the crimes committed. This research found that can also be exploited by criminals to collaborate in carrying out their actions. The analysis was carried out using the EUCPN family-basec crime scheme formulated by Anna Sergi and colleagues. In order to develop a strategy to prevent organized narcotics crime on a family basis, the author tries to offer strengthening family resilience as promoted by Froma Walsh. This is interesting to discuss considering the presence of the Fredy Pratama phenomenon in Indonesia which challenges the concept of the ideal family as a protector for family members, as well as the lack of research related to organized narcotics crime on a family basis. This research is presented using qualitative methods through a literacy study approach.